Specifics of the Polish-Belarusian economic relations in the 21st century - Łukasz Wojcieszak (CES Working Papers, 2017)
The article deals with the relations between Poland and Belarus in the 21st century in the light of the recent events showing the re-rapprochement between the two countries. The aim of the paper is to present the importance of economic cooperation and the development of trade relations for the strengthening of the relations between these countries. The author emphasizes cooperation in the energy sector. He describes how crucial trade and economic cooperation is in overcoming crises in political relations. The author stresses the role of Poland in supporting the economic transformation of Belarus creating an alternative to the cooperation between Belarus and Russia. In this article the author uses descriptions, as well as the predictive methods.
Keywords: 330; Poland; Belarus; economic relations